Prinsip-Prinsip Penginjilan yang Efektif Menurut Kisah Para Rasul 13:1-12 Bagi Pertumbuhan Gereja Masa Kini - Paulus Kunto Baskoro (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2022)
The power of an evangelism is an important key to church growth. Evangelism is a step in preaching the gospel of Christ Jesus to every person and all nation. Because when people accept Jesus as their Lord and Savior, their lives change. The church must understand that the most important thing in a ministry is that many souls are saved and discipled. That’s why to understand the principles of effective evangelism the author reliaes on the understanding an Acts 13:1-12 which is a strong reference from the example of the early church. The method used is descriptive literature method. This research will discuss about effective ways of evangelism, so that evangelism is more effective and can be apllied in all ages. The purpose of this writing is First, to explore effective principles in evangelism according Acts 13:1-12. Second, apply or aplly the principles of evangelism that are effective for the growth of the church today. Third, help equip every church leader to continue to be faithful in carrying out evangelism, according to the great commission.